CALPHAD-guided alloy design and processing for improved strength and toughness in Titanium Boride (TiB) ceramic alloy containing a ductile phase. (1st June 2019) - Du, J.; Jindal, V.; Sanders, A.P.; Ravi Chandran, K.S.
Abstract: A CALPHAD-guided alloy design strategy is used here to design and process fully dense titanium boride (TiB) ceramic alloys containing a ductile phase for toughening. This involved the construction of high temperature phase fields of the Ti-B-Fe-Mo quaternary alloy system using the CALPAHD approach. To design the compositions, ternary phase diagrams of Ti-B-Fe, Ti-B-Mo, and Fe-Mo-B systems were first constructed using the thermodynamic databases that were verified to predict well the binary phase diagrams of components. Using this as a basis, the pseudo-ternary diagrams of the Ti-B-Fe-Mo system were constructed to map the high temperature phase fields over a wide range of composition. This made it possible to identify relatively lower reaction sintering temperatures for various alloy compositions. Two compositions of TiB ceramic alloys with the ductile beta-phase (both having ∼85% TiB and ∼15% β-Ti phase), were considered for the demonstration of the present approach. Based on the pseudo-ternary phase fields, these two compositions could be processed using electric-field-activated sintering (EFAS), in a relatively short time, at their respective liquid-phase-forming temperatures. The processing temperature was as low as 1423 K for a Fe/Mo-rich ceramic alloy composition, but the formation of brittle intermetallic phase FeTi here was found to be detrimental to mechanical properties. The second TiB ceramic alloy composition, which was Fe/Mo-lean, could be processed at 1623 K. This composition is shown here to possess a very good combination of high flexural strength (∼850 MPa) and high fracture toughness (∼7.7 MPa√m), making it attractive for potential applications. The identification of the liquid phase reaction sintering regions in the ternary phase diagrams, and the eventual finding of one composition giving a relatively high strength and toughness, demonstrate that this is an effective approach for alloy design. The microstructural factors that control the strength and toughness have been identified and the ways to increase these properties further, in this class of materials, are suggested. Graphical abstract: Image 1